المثل الشعبي في منطقة وادي سوف ودوره في الحفاظ على الهوية الوطنية - مداني، علاء; محريق، ساسية; مداني، عائشة; ناني، سليمة (My University, 2024)
الملخص: ما من أمة الا وتملك ثقافة شعبية، تحفظ ماضيها وتراثها الثقافي، تعكس رايتها للعامة ونظامه الأخلاقي، ومرجعتيها الفكرية لتي تنبع من أصولها وتعبر عن أسلافها الأوائل الذين يحظون بالتقديس وتمجيد والتبجيل في كل الثقافات ولى كل الجماعات الثقافية. إن الأدب الشعبي هو شكل من اشكال التواصل الاجتماعي يعبر عن رغبة المحمومة في بناء هوية ثقافية جماعية قادرة على حفظ وحدة الجماعة وقيمها ونمط عيشها وتقاليدها، وتعد الامثال الشعبية احدى هذه الاشكال التي تشترط علينا الحفاظ عليها، لما تتضمنه من مفاهيم وصور لشخصية المجتمع، إنها العدسة التي تسلط الأضواء، لتكشف لنا مختلف القيم التي تلعب دوراً فاعلاً في تحديد سلوك الفرد، وتوجيهه في المجتمع، خاصة الامثال الشعبية في منطقتنا (الوادي) التي تشتمل على مجموعة من لقيم الدينية، الاجتماعية، والأخلاقية لتي تستطيع بها أن نبني قيمن ومعتقدتنا وتوجه سلوكنا إلى الأحسن والأفضل. وتسعى هذه الدراسة إلى ملامسة وإبراز الدور هذا الموروث الشعبي الامثال الشعبية) في تعزيز الهوية الوطنية والمحافظة عليها من الاندثار لكونه مخزونها الروحي والثقافي وذلك بالتركيز على اهم القيم الدينية والاجتماعية والأخلاقية في حياتنا اليومية ومن هنا نطرح التساؤلات التالية: هل المثل الشعبي السوفي لا يزال يحافظ على حضوره الدائم داخل الأوساط الشعبية؟ وما هو دوره في توجيه سلوك الفرد والحفاظ على هويته There is no nation that possesses only a popular culture that preserves its past and cultural heritage, reflects its flag to the public and its moral system, and its intellectual references that stem from its origins and reflect its early ancestors who are revered, glorified and revered in all cultures and all cultural groups. Folk literature is a form of social communication that expresses a frantic desire to build a collective cultural identity capable of preserving the unity of the group, its values, lifestyle and traditions, and folk proverbs are one of these forms that require us to preserve it, because it includes concepts and images of the personality of society. it is the lens that sheds light, to reveal to us the various values that play an active role in determining the behavior of an individual, and guiding him in society, especially folk proverbs in our region (EL- OUED), which includes a set of religious, social, and moral values, so that with it, we can build our values and beliefs and direct our behavior to the best and the best. This study seeks to touch and highlight the role of this folk heritage (folk proverbs) in strengthening the national identity and preserving it from extinction because it is its spiritual and cultural stock by focusing on the most important religious, social and moral values in our daily lives, and hence we ask the following questions: Does the Soviet folk proverb still maintain its permanent presence within popular circles And what is its role in guiding the behavior of the individual and preserving his identity
398/ 006
Keywords: روث الشعبي الامثال الشعبية - الهوية الوطنية القيم الأخلاقية والدنية والاجتماعية .... الخ; Folk Heritage-folk Proverbs-national identity-moral; religious and social values...Etc